Synthesis, conformational control, and photothermal application of helically twisted 3,6-carbazole-based porphyrinoids and mono-palladium complex - Chengming Li; Weihua Zhuang; Yongjie Zhou; Linfeng He; Jiayin Yang; Gang Xu; Rongchuan Su; Mao Chen; Jingsong You (Nature Communications)
Abstract Synthetic control over multiple conformations of expanded porphyrinoids, which are intrinsically linked to their properties and functions, has long been a key objective in chemical research. Here, we present an N-substituent-controlled synthesis of 3,6-carbazole-based octaphyrins and dodecaphyrins via modified Rothemund-type condensation. The choice of pre-modified N-substituents (hydrogen, methyl, tert-butoxycarbonyl) on the 3,6-carbazolylene precursors critically dictates the assembly pathway, enabling access to porphyrinoids with distinct conformations. The octaphyrin scaffold comprises two figure-eight geometries and a half-twisted Möbius form, shaped by solvent-drived kinetic and thermodynamic control. The dodecaphyrins display two helically twisted topologies governed by thermodynamical control. Metalation with Pd(OAc)₂ stabilizes the dynamic twist of octaphyrin into a specific figure-eight geometry, yielding a mono-PdII complex featuring an unconventional NNCC–Pd coordination mode. All these systems exhibit pronounced optical responses to near-infrared light and the mono-PdII complex demonstrates efficient photothermal conversion after encapsulation within nanoparticles, allowing for tumor phototheranostics in the near-infrared bio-window.